Histomorphological Profile of Liver and Kidney Tissues of Albino Wistar Rats Following Exposure to Cadmium-Induced Damage and Ascorbic Acid Supplementation - Uche C. Okwuonu; Dayo R. Omotoso; Emmanuel O. Bienonwu; Osahenrhumwen Adagbonyin; Joseph Dappa (Academia Anatomica International, 2020)
Introduction: Cadmium is a common heavy metal toxicant that can cause diverse tissue toxicities and pathologies. Conversely, ascorbic acid is a natural anti-oxidant that can ameliorate cytotoxic effects of tissue toxicants.  In this study, the objective was to assess the histomorphological profile of liver and kidney tissues of albino Wistar rats after exposure to cadmium-induced damage and ascorbic acid supplementation. Subjects and Methods: 24 animals were divided into four groups (1-4) comprising of six animals each (n=6). Normal control group 1 was given distilled water, test control group 2 given 5 mg/kg Cadmium chloride and test groups 3 and 4 given 5 mg/kg Cadmium chloride + 100 mg/kg ascorbic acid and 5 mg/kg + 200 mg/kg ascorbic acid respectively. The route of the 21 days administration was oral. Thereafter, the liver and kidney of experimental animals were harvested, weighed and processed.  Results: Only the test control group 2 showed significant (p < 0.05) reduction in mean organ weight compared to normal control group 1.  Similarly, only the test control group 2 animals showed significant alterations in the liver and kidney histomorphological profile compared to normal control group 1. Conclusion: The ascorbic acid exhibited prominent ameliorative effect against damaging effect of cadmium exposure leading to relative reparation of liver and kidney histomorphology in albino Wistar rats.